1994
DOI: 10.1007/bf01878119
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative responses towards native, heat-denatured and pepsin-treated ovalbumin by peripheral blood mononuclear cells from patients with hen's egg-sensitive atopic dermatitis

Abstract: In order to clarify the mechanism of food-antigen recognition, the proliferative responses of peripheral blood mononuclear cells (PBMCs) to native, heat-denatured or pepsin-treated ovalbumin (OA) were investigated in 16 hen's egg-sensitive patients with atopic dermatitis (AD). Seven of them had hypersensitivity to boiled hen's egg and others had not. The responses of PBMCs to heat-denatured OA were lower than those to native OA in the patients without hypersensitivity to boiled hen's egg. However, there were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The control experiment was repeated three times and determined to have no effect on cell proliferation. This is consistent with other studies that have used different cell lines and showed no proliferation response after treatment with ovalbumin. …”
Section: Results and Discussionsupporting
confidence: 93%
“…The control experiment was repeated three times and determined to have no effect on cell proliferation. This is consistent with other studies that have used different cell lines and showed no proliferation response after treatment with ovalbumin. …”
Section: Results and Discussionsupporting
confidence: 93%
“…Our findings suggest that new solid phase immunosolvent assays or in vitro histamine release assays using heat treated and/or digested food proteins may provide further information on food hypersensitivity, especially in children with IgE specific to food proteins. In fact, the use of enzyme‐digested egg proteins in patients with egg allergy is useful for predicting clinical symptoms or their resolution [45, 46]. Using heat treatment in addition to enzymatic digestion may improve the diagnostic value of this kind of assay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OVA is an often used model antigen for immunological studies and several studies have characterized epitopes on the protein, e.g. in relation to allergy . OVA is a serpin (serin protease inhibitor), belonging to a large protein family, the members of which undergo structural changes upon protease binding .…”
mentioning
confidence: 99%